Pemanfaatan Moodle dalam Pembelajaran Sharaf dan Interaksinya dengan Locus of Control (LOC) Mahasiswa - Rahmat, Aceng Rahmat (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2014)
The study examines the effectiveness of Moodle in teaching Sharaf (Arabic morphology) by taking into account the students’ locus of control (LOC). A 2×2 factorial design was used in this study. In general, the group of students who were taught by using Moodle showed higher scores than the group who were taught without using Moodle. When the students’ LOC were taken into consideration, however, the students with external LOC in the Moodle group showed lower scores than those with external LOC in the non-Moodle group. The opposite was true for the students with internal LOC. It can be concluded that using Moodle in teaching Sharaf was effective when the students have internal LOC, but not effective when they have external LOC. Considering the students have internal LOC, the use of Moodle can improve the quality of teaching Sharaf and the students’ scores.